Recent Development of Herbal Gel by Combination of Medicinal Plants in the Treatment of Periodontitis - Rathore, Charul; Kumar, Ashok; Pendyala, Vijetha; Jilani, Abdul Kadir; Mukherjee, Rajesh Kumar; Badal, Shailendra; Bansal, Sagar (Journal of Neonatal Surgery, 2025)
Aim: The purpose of this research is to create a herbal gel with extracts of turmeric, aloe vera, and Glycyrrhiza glabra and assess how well it works to treat periodontitis. The study intends to evaluate the gel's antibacterial, anti-inflammatory, and wound-healing capabilities both in vitro and in vivo. Materials & Methods: Preparation of Herbal Gel: Extracts of Glycyrrhiza glabra, Aloe Vera, and Turmeric were obtained and formulated into a gel base using appropriate excipients. In vitro Evaluation: The gel's antimicrobial activity against periodontal pathogens was assessed using agar diffusion methods. Its anti-inflammatory activity was evaluated through inhibition of inflammatory markers in cell culture models. In vivo Evaluation: Animal model (rats) of periodontitis was treated with the herbal gel, and parameters including gingival index, probing depth, and attachment loss were measured to assess its therapeutic efficacy. Results & Discussion: In vitro Results: The herbal gel demonstrated strong antibacterial action against periodontal infections, with minimum inhibitory concentrations and a zone of inhibition that were on par with those of traditional antibiotics. It also showed strong anti-inflammatory properties. Impacts by inhibiting the production of cytokines that promotes inflammation. In vivo Results: Treatment with the herbal gel resulted in reduced gingival inflammation, decreased probing depth, and improved attachment gain. Conclusion: Glycyrrhiza glabra, aloe vera, and turmeric combined in a herbal gel formulation have encouraging promise for treating periodontitis. Both in vitro and in vivo, the gel demonstrates potent antibacterial, anti-inflammatory, and wound-healing qualities. Additionally Clinical research is necessary to confirm its safety and effectiveness for human use. This herbal approach offers a natural and potentially safer alternative to conventional treatment modalities for periodontitis